2009
DOI: 10.1038/ncb2006
|View full text |Cite
|
Sign up to set email alerts
|

A bacterial E3 ubiquitin ligase IpaH9.8 targets NEMO/IKKγ to dampen the host NF-κB-mediated inflammatory response

Abstract: NF-κB (nuclear factor κB) has a pivotal role in many cellular processes, including the inflammatory and immune responses and, therefore, its activation is tightly regulated by the IKK (IκB kinase) complex and by IκBα degradation. When Shigella bacteria multiply within epithelial cells they release peptidoglycans, which are recognized by Nod1 and stimulate the NF-κB pathway, thus leading to a severe inflammatory response. Here, we show that IpaH9.8, a Shigella effector possessing E3 ligase activity, dampens the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
197
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(203 citation statements)
references
References 34 publications
5
197
1
Order By: Relevance
“…Moreover, recently, it was reported that bacterial E3 ligase IpaH9.8 promotes K27-linked ubiquitin conjugation to NEMO and facilitates degradation of NEMO with unidentified molecule(s) activated by NOD1 signaling (37). Although both E3 ligases, TRIM23, and bacterially encoded IpaH9.8 conjugate K27-linked ubiquitin to NEMO, the outcomes are totally different.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, recently, it was reported that bacterial E3 ligase IpaH9.8 promotes K27-linked ubiquitin conjugation to NEMO and facilitates degradation of NEMO with unidentified molecule(s) activated by NOD1 signaling (37). Although both E3 ligases, TRIM23, and bacterially encoded IpaH9.8 conjugate K27-linked ubiquitin to NEMO, the outcomes are totally different.…”
Section: Discussionmentioning
confidence: 96%
“…Enteropathogenic Escherichia coli (EPEC) also has been shown to prevent the phosphorylation of IκB through the use of two T3SS effectors, NleE and NleB, which interact with the TAK1-IKK A B pathway, albeit in an unknown fashion (38). Finally, Shigella has at least two effectors, OspG and IpaH9.8, that interfere with the NF-κB pathway (25,39). IpaH9.8 is an ubiquitin ligase that interacts and interferes with NEMO, thereby impairing IκB phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…102 Certain NEL family members, including IpaH9.8, IpaH0722 and IpaH4.5, have been shown to tamper with the host NF-κB cascade by ubiquitinating NEMO, TRAF2 and p65 for proteasomal degradation, respectively. [103][104][105] Another NEL effector, IpaH7.8, possesses E3 ligase activity in vitro and targets an inhibitor of Cullin-based RING E3 ligase named GLMN for degradation, which augments inflammasome activation. 106 In addition, OspG and OspI, belonging to a different subsets of S. flexneri effectors, have recently been identified to suppress NF-κB activation by disrupting the ubiquitin system.…”
Section: Shigella Flexnerimentioning
confidence: 99%